A Comparative Analysis: Heuristic Self-Search Inquiry as Self-Knowledge and Knowledge of Society. (May 2017) - Ozertugrul, Engin
In research, the standard view of credibility seeks to illuminate what the researcher did with the data vis-à-vis collection, analysis, and interpretation. This works well in standard research where data can be checked through conventional validity measures (internal validity, external validity, reliability, replicability, and objectivity). It does not work well in heuristic self-search inquiry (HSSI) method where the data are in the researcher. In previous HSSI works, there is a level of uncertainty regarding the use of the method in knowledge exploration. It seems that there is still a need for the development of methodological understanding, particularly in terms of those who favor the use of multiple participants in HSSI, as opposed to those who do not. In this article, I compared four studies to clarify HSSI's utility in knowledge production for future use.